2023
DOI: 10.2147/ijgm.s393273
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Total Bilirubin, Total Bilirubin/Albumin Ratio with Disease Activity in Patients with Rheumatoid Arthritis

Abstract: Purpose Rheumatoid arthritis (RA) is a systemic inflammatory disorder with unknown etiology. Oxidative stress and immune imbalance play a critical role in the pathogenesis of rheumatoid arthritis. Bilirubin has recently been recognized as a potent antioxidant as well as an immunomodulatory agent of physiological importance. The aim of this study was to explore whether increased bilirubin concentrations are correlated with good clinical prognosis of rheumatoid arthritis. Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…From a total of 2,805 articles initially identified, 2,783 were excluded because they were either duplicates or irrelevant. After a full-text review of the remaining 22 articles, a further two were excluded because of missing data and three because they did not have a case-control design, leaving 17 studies for further analysis ( 33 49 ) ( Figure 1 ; Table 1 ). The risk of bias was considered low in all studies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 2,805 articles initially identified, 2,783 were excluded because they were either duplicates or irrelevant. After a full-text review of the remaining 22 articles, a further two were excluded because of missing data and three because they did not have a case-control design, leaving 17 studies for further analysis ( 33 49 ) ( Figure 1 ; Table 1 ). The risk of bias was considered low in all studies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of bilirubin was described as inversely proportional to the disease activity [46]. Thus, the increased concentration of bilirubin within the physiological range after an efficient treatment start might indicate the beneficial effect of the treatment that might be supported by the antioxidant effects of bilirubin [46,47]. Based on the literature, we expected an effect on liver enzymes [48].…”
Section: Discussionmentioning
confidence: 97%
“…According to the literature, the concentration of bilirubin in RA patients was described as lower compared to healthy individuals [45]. The concentration of bilirubin was described as inversely proportional to the disease activity [46]. Thus, the increased concentration of bilirubin within the physiological range after an efficient treatment start might indicate the beneficial effect of the treatment that might be supported by the antioxidant effects of bilirubin [46,47].…”
Section: Discussionmentioning
confidence: 99%
“… 2 Oxidative stress generates excessive free radicals that oxidize other molecules in the body, for example, excessive free radicals in RA patients reduce the antioxidant level of the body and accelerate the progression of bone destruction. 3 We demonstrated that the low expression of LINC00638 regulates the Nrf2/HO‐1 signaling pathway, triggering inflammation in RA and influencing its oxidative stress response. 4 The Nrf2/HO‐1 signaling pathway can also affect antioxidant enzymes, regulate cellular redox responses, and influence other antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 85%
“…Activated fibroblastic synoviocytes (FLS), and inflammatory and oxidative factors are found to be involved in the inflammatory mechanisms of RA during the bone destruction and synovitis of RA 2 . Oxidative stress generates excessive free radicals that oxidize other molecules in the body, for example, excessive free radicals in RA patients reduce the antioxidant level of the body and accelerate the progression of bone destruction 3 . We demonstrated that the low expression of LINC00638 regulates the Nrf2/HO‐1 signaling pathway, triggering inflammation in RA and influencing its oxidative stress response 4 .…”
Section: Introductionmentioning
confidence: 99%